GLOBAL DISTRIBUTION OF GENETIC DISEASES BY GEOGRAPHIC REGIONS AND PREVENTIVE STRATEGIES - Y.Kabilova; K.Saydullayeva (Modern World Education: New Age Problems – New solutions, 2026)
Genetic diseases constitute a significant global health burden, affecting millions of individuals worldwide. Their distribution varies considerably across geographic regions due to differences in genetic background, population structure, consanguinity rates, environmental factors, and access to healthcare services. This review analyzes the global distribution of genetic diseases by regions and discusses current preventive strategies, including genetic screening, counseling, and public health interventions. Understanding regional epidemiological patterns is essential for effective prevention, early diagnosis, and reduction of disease-related morbidity and mortality.